Metal compound doped PZT-based piezoelectric ceramic material with high piezoelectric constant and ultralow-temperature sintering preparation method of metal compound doped PZT-based piezoelectric ceramic material

By doping metal compounds in Pzt base pressure electrical ceramic materials, the sintering temperature is reduced to 860 ° C ~ 920 ° C, the problem of high sintering temperature for voltage -electrical ceramic materials in existing technology, realizing high -voltage electricity constant and high electrical coupling coupling The preparation of coefficients of ceramic materials reduces production costs and improves device reliability.

CN119350021APending Publication Date: 2025-01-24ZHEJIANG JIAKANG ELECTRONICS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411471452.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The sintering temperature of existing piezoelectric ceramic materials is generally as high as 1200℃, which cannot meet the requirements of co-firing of stacked piezoelectric ceramics and silver paste, resulting in a decrease in insulation of ceramic materials and an increase in production costs.

Method used

By doping PZT-based piezoelectric ceramic materials with metal compounds such as ZnO, Li2CO3 and CeO2, the chemical composition ratio of the material is adjusted, the sintering temperature is lowered to 860℃~920℃, and the high voltage electric constant d33≥500pC is maintained at this temperature. /N and high electromechanical coupling coefficient Kp≥0.6.

Benefits of technology

It is possible to prepare piezoelectric ceramic materials with high voltage electrical constants and high electromechanical coupling coefficients at temperatures below 900°C, which reduces production costs and improves the reliability of multilayer piezoelectric ceramic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350021A_ABST
    Figure CN119350021A_ABST
Patent Text Reader

Abstract

The invention discloses a metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant and an ultralow-temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material, and belongs to the technical field of piezoelectric ceramics. The general chemical formula of the piezoelectric ceramic material is Pb1-xLax (Ni1 / 3Nb2 / 3) y (Mg1 / 3Nb2 / 3) zZrmTinO3 + v% MO, MO is a doped metal compound, v% ranges from 0.4 wt% to 1.0 wt%, and the metal compound MO is ZnO, Li2CO3 and CeO2. By designing the proportion of the main chemical components of the ceramic material and doping the metal compound, the sintering temperature of the piezoelectric ceramic material is reduced to 860-920 DEG C, and the piezoelectric ceramic material with the high piezoelectric constant is still obtained when the low sintering temperature is adopted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of piezoelectric ceramics, and in particular to a metal compound-doped PZT-based piezoelectric ceramic material with a high piezoelectric constant and an ultra-low temperature sintering preparation method thereof. Background Art

[0002] With the development of technology, the miniaturization and intelligence of various electronic devices are developing rapidly. Piezoelectric ceramics are functional ceramic materials that can convert mechanical energy into electrical energy. Their applications in brakes, converters, and sensors are becoming more and more extensive. Multilayer piezoelectric ceramics are the main way to prepare piezoelectric devices in a miniaturized manner. Since the sintering temperature of piezoelectric ceramics is generally 1200°C, there are considerable restrictions on the preparation of laminated co-fired piezoelectric ceramics. Because the electrodes in laminated piezoelectric ceramics are silver electrodes, and the melting point of silver is low, excessive sintering temperature will cause metal ions to diffuse into the ceramic layer, thereby reducing the insulation of the ceramic material. In order to solve this problem, Ag-Pd slurry is needed to make electrodes. However, due to the addition of pd, the production cost of piezoelectric multilayer ceramic components is greatly increased. In order to reduce production costs, the sintering temperature of piezoelectric ceramics can only be reduced to reduce the migration of electrode metal ions and improve the reliability of multilayer piezoelectric ceramic devices. For multilayer piezoelectric ceramic devices, the higher the piezoelectric constant, the greater the displacement of the brake and the more sensitive the sensor signal.

[0003] In summary, developing low-temperature sintered piezoelectric ceramic materials so that they have a high piezoelectric constant d33 ≥ 500pC / N and a high electromechanical coupling coefficient Kp ≥ 0.6 after sintering at a temperature below 900°C is a difficult problem in the field of piezoelectric ceramics. Summary of the invention

[0004] In view of the fact that the sintering temperature of existing piezoelectric ceramic materials is generally as high as about 1200°C and cannot meet the current requirements for co-firing of laminated piezoelectric ceramics and silver paste, the purpose of the present invention is to provide a metal compound-doped PZT-based piezoelectric ceramic material with a high piezoelectric constant and a method for preparing the same by ultra-low temperature sintering. The present invention improves the ceramic material formula so that a piezoelectric ceramic material with a high piezoelectric constant can still be obtained when a lower sintering temperature is used.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant, the chemical formula of which is Pb 1-x La x (Ni 1 / 3 Nb 2 / 3 ) y (Mg 1 / 3 Nb 2 / 3 ) zZr m Ti n O3+v%MO, wherein 0.01≤x≤0.03, 0.1≤y≤0.2, 0.2≤z≤0.3, 0.2≤m≤0.3, n=1-(y+z+m), MO is a doped metal compound, and v% ranges from 0.4 to 1.0wt.%, v% represents the doping amount of MO in PZT-based piezoelectric ceramics (Pb 1-x La x (Ni 1 / 3 Nb 2 / 3 ) y (Mg 1 / 3 Nb 2 / 3 ) z Zr m Ti n O3) weight percentage.

[0007] Furthermore, the metal compound MO is ZnO, Li2CO3 and CeO2, the doping amount of ZnO is 0.1-0.4wt.%, the doping amount of Li2CO3 is 0.1-0.4wt.%, and the doping amount of CeO2 is 0.15-0.5wt.%.

[0008] Furthermore, the piezoelectric constant d33 of the metal compound doped PZT-based piezoelectric ceramic material is ≥500pC / N, and the electromechanical coupling coefficient K p ≥0.6.

[0009] When preparing the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant, a low sintering temperature of 860-920° C. is adopted; the preparation method specifically comprises the following steps:

[0010] (1) Ingredients: weigh the raw materials Pb3O4, ZrO2, TiO2, Ni2O3, Nb2O5, Mg(OH)2 and doped metal compounds (Li2CO3, ZnO, CeO2) according to the general chemical formula of the piezoelectric ceramic material;

[0011] (2) Mixing: The weighed raw materials are pre-mixed and then subjected to planetary ball milling. The ball milling medium is zirconium balls and deionized water. After ball milling, the mixture is placed in an oven at 150° C. and dried for 12 hours to obtain a dry powder.

[0012] (3) Pre-sintering: placing the dried powder obtained in step (2) in an alumina crucible and pre-sintering in a carbon rod furnace at 750-780° C. for 2-4 hours;

[0013] (4) slurry preparation: the material obtained after pre-calcination in step (3) is milled in a planetary ball mill for 2 to 3 hours, the milling medium being zirconium balls and deionized water, to obtain a viscous slurry after ball milling;

[0014] (5) Sintering: Add 7-10 wt% of a binder to the slurry obtained in step (4) and spray granulate it, then press it into shape, and finally heat it to 860-920°C in a carbon rod furnace and keep it warm for 3 hours; the binder is a polyvinyl alcohol aqueous solution with a concentration of 5-15 wt%.

[0015] (6) Polarization: The sintered samples were polarized under the following conditions: polarization temperature of 100-130°C, polarization voltage of 3.0-4.5 kV / mm, and polarization time of 30-50 minutes.

[0016] Furthermore, when the sintering temperature is 860-920°C, the piezoelectric constant d33 of the material is ≥500pC / N, K p ≥0.6; Specifically, when sintered at 860°C, the piezoelectric constant d33 of the material is ≥500pC / N, K p ≥0.6, when sintered at 880℃, the piezoelectric constant d33 of the material is ≥550pC / N, K p ≥0.6, when sintered at 900℃, the piezoelectric constant d33 of the material is ≥600pC / N, K p ≥0.6, when sintered at 920℃, the piezoelectric constant d33 of the material is ≥650pC / N, K p ≥0.6.

[0017] The design mechanism and beneficial effects of the present invention are as follows:

[0018] 1. At present, the laminated piezoelectric ceramic materials are co-fired with silver paste and ceramics. Since the sintering temperature of piezoelectric ceramic materials is generally 1200℃, and the highest sintering temperature of ordinary silver paste is 850℃, the temperature difference between the two is too large, resulting in the inability to co-fire. In order to enable piezoelectric ceramics and silver paste to be co-fired together, the sintering temperature of piezoelectric ceramics can only be reduced or the sintering temperature of silver paste can be increased. The method to increase the sintering temperature of silver paste is to use palladium-silver paste. The higher the palladium-silver content, the higher the silver sintering temperature. The price of palladium-silver paste is very high, which greatly increases the production cost. The present invention can reduce the sintering temperature of piezoelectric ceramic materials to 860℃~920℃ and has excellent piezoelectric properties. When the sintering temperature is 860℃, ordinary silver paste or silver paste containing a small amount of palladium can be used, thereby greatly reducing the production cost of such products.

[0019] 2. The present invention improves the piezoelectric properties of piezoelectric ceramic materials by doping modification while reducing the sintering temperature of piezoelectric ceramics.

[0020] 3. The present invention reduces the sintering temperature of piezoelectric ceramic materials to 860°C by designing the ratio of the main chemical components and then doping with metal compounds. When sintered at 860°C, the piezoelectric performance of the material is d33≥500pC / N, K p≥0.6; when the sintering temperature is 920℃, the piezoelectric constant d33 can be as high as 650pC / N.

[0021] 4. The metal compound MO doped in the ceramic formula of the present invention is modified by mainly doping CeO2, with Li2CO3 and ZnO as auxiliary, so as to improve the piezoelectric properties of the piezoelectric ceramic material while reducing the sintering temperature.

[0022] 5. The ceramic formula of the present invention is based on PZT-based piezoelectric ceramic Pb 1-x La x (Ni 1 / 3 Nb 2 / 3 ) y (Mg 1 / 3 Nb 2 / 3 ) z Zr m Ti n O is added to CeO2, Li2CO3, and ZnO metal compounds according to weight ratio, and the sintering temperature is reduced to 860℃. The piezoelectric constant d33 of the obtained ceramic material is ≥500pC / N, K p ≥0.6, when the sintering temperature is reduced to 880℃, the piezoelectric constant d33 of the obtained material is ≥550pC / N, K p ≥0.6, when the sintering temperature is reduced to 900℃, the piezoelectric constant d33 of the obtained material is ≥600pC / N, K p ≥0.6, when the sintering temperature is reduced to 920℃, the piezoelectric constant d33 of the obtained material is ≥650pC / N, K p ≥0.6. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are 2400x laser microscope grain photographs of the ceramic materials of Examples 1-4 after sintering at 860°C; among them: (a) Example 1; (b) Example 2; (c) Example 3; (d) Example 4.

[0024] Figure 2 The XRD diffraction patterns of the ceramic materials of Examples 1-4 after sintering at 860°C. DETAILED DESCRIPTION

[0025] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with the embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0026] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0027] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0028] The present invention provides a piezoelectric ceramic material doped with a metal compound prepared by low temperature sintering, the chemical formula of which is Pb 1-x La x (Ni 1 / 3 Nb 2 / 3 ) y (Mg 1 / 3 Nb 2 / 3 ) z Zr m Ti n O3+v%MO, wherein 0.0≤x≤0.03, 0≤y≤0.2, 0≤z≤0.3, 0≤m≤0.3, n=1-(y+z+m); v% ranges from 0.4 to 1wt%, and MO is a metal compound such as ZnO, Li2CO3, or CeO2, wherein the doping amount of ZnO is 0.1 to 0.4wt%, the doping amount of Li2CO3 is 0.1 to 0.4wt%, and the doping amount of CeO2 is 0.15 to 0.5wt%, and the ceramic is mainly modified by doping with CeO2, Li2CO3, and ZnO metal compounds to reduce the sintering temperature while improving the piezoelectric properties of the ceramic.

[0029] The ultra-low temperature sintered high-voltage piezoelectric constant piezoelectric ceramic material of the embodiment of the present invention has a sintering temperature of 860°C to 920°C, d33≥500pC / N, K p ≥0.6.

[0030] The binder used in the following examples is a polyvinyl alcohol aqueous solution with a concentration of 10 wt.%.

[0031] Embodiment 1:

[0032] This embodiment provides a method for preparing an ultra-low temperature sintered piezoelectric ceramic material with a high voltage constant, comprising the following steps:

[0033] A. Ingredients: According to the chemical formula Pb 0.99 La 0.01 (Ni 1 / 3 Nb 2 / 3 ) 0.15 (Mg 1 / 3 Nb 2 / 3 ) 0.2 1Zr 0.3 Ti 0.34O3+0.25wt%ZnO+0.26wt%Li2CO3+0.1wt%CeO2 Calculation Weigh Pb3O4, ZrO2, TiO2, Ni2O3, Nb2O5, Mg(OH)2 and doped metal compounds such as Li2CO3, ZnO, and CeO2;

[0034] B. Mixing: The raw materials are pre-mixed and then subjected to planetary ball milling. The ball milling medium is zirconium balls and deionized water. The raw materials are then placed in an oven at 150° C. and dried for 12 hours to obtain dry powder.

[0035] C. Pre-sintering: Place the dried powder in an alumina crucible and pre-sinter in a carbon rod furnace at 750°C for 3 hours to obtain a raw material powder;

[0036] D. Slurry making: the raw material powder is milled by a planetary ball mill for 3 hours, the ball milling medium is zirconium balls and deionized water, and a viscous slurry is obtained;

[0037] E. Molding: Add 8 wt% of a binder to the slurry and spray granulate it, then press it into shape, and finally keep it in a carbon rod furnace at 860° C., 880° C., 900° C., and 920° C. for 3 hours.

[0038] F. Polarization: The polarization conditions are as follows: polarization temperature is 120° C., polarization voltage is 4 kV / mm, and polarization time is 45 minutes.

[0039] Embodiment 2:

[0040] This embodiment provides a method for preparing an ultra-low temperature sintered piezoelectric ceramic material with a high voltage constant, comprising the following steps:

[0041] A. Ingredients: According to the chemical formula Pb 0.98 La 0.2 (Ni 1 / 3 Nb 2 / 3 ) 0.15 (Mg 1 / 3 Nb 2 / 3 ) 0.21 Zr 0.3 Ti 0.34 O3+0.2wt%ZnO+0.2wt%LiCO3+0.2wt%CeO2 Calculation Weigh Pb3O4, ZrO2, TiO2, Ni2O3, Nb2O5, Mg(OH)2 and Li2CO3, ZnO, CeO2 doped metal compounds;

[0042] B. Mixing: The raw materials are pre-mixed and then subjected to planetary ball milling. The ball milling medium is zirconium balls and deionized water. The raw materials are then placed in an oven at 150° C. and dried for 12 hours to obtain dry powder.

[0043] C. Pre-sintering: Place the dried powder in an alumina crucible and pre-sinter in a carbon rod furnace at 750°C for 3 hours to obtain a raw material powder;

[0044] D. Slurry making: the raw material powder is milled by a planetary ball mill for 3 hours, the ball milling medium is zirconium balls and deionized water, and a viscous slurry is obtained;

[0045] E. Molding: Add 8 wt% of a binder to the slurry and spray granulate it, then press it into shape, and finally keep it in a carbon rod furnace at 860° C., 880° C., 900° C., and 920° C. for 3 hours.

[0046] F. Polarization: The polarization conditions are as follows: polarization temperature is 120° C., polarization voltage is 4 kV / mm, and polarization time is 45 minutes.

[0047] Embodiment 3:

[0048] This embodiment provides a method for preparing an ultra-low temperature sintered piezoelectric ceramic material with a high voltage constant, comprising the following steps:

[0049] A. Ingredients: According to the chemical formula Pb 0.98 La 0.2 (Ni 1 / 3 Nb 2 / 3 ) 0.15 (Mg 1 / 3 Nb 2 / 3 ) 0.21 Zr 0.3 Ti 0.34 O3+0.25wt%ZnO+0.26wt%Li2CO3+0.3wt%CeO2 Calculation Weigh Pb3O4, ZrO2, TiO2, Ni2O3, Nb2O5, Mg(OH)2 and Li2CO3, ZnO, CeO2 doped metal compounds;

[0050] B. Mixing: The raw materials are pre-mixed and then subjected to planetary ball milling. The ball milling medium is zirconium balls and deionized water. The raw materials are then placed in an oven at 150° C. and dried for 12 hours to obtain dry powder.

[0051] C. Pre-sintering: Place the dried powder in an alumina crucible and pre-sinter in a carbon rod furnace at 750°C for 3 hours to obtain a raw material powder;

[0052] D. Slurry making: the raw material powder is milled by a planetary ball mill for 3 hours, the ball milling medium is zirconium balls and deionized water, and a viscous slurry is obtained;

[0053] E. Molding: Add 8 wt% of a binder to the slurry and spray granulate it, then press it into shape, and finally keep it in a carbon rod furnace at 860° C., 880° C., 900° C., and 920° C. for 3 hours.

[0054] F. Polarization: The polarization conditions are as follows: polarization temperature is 120° C., polarization voltage is 4 kV / mm, and polarization time is 45 minutes.

[0055] Embodiment 4:

[0056] This embodiment provides a method for preparing an ultra-low temperature sintered piezoelectric ceramic material with a high voltage constant, comprising the following steps:

[0057] A. Ingredients: According to the chemical formula Pb 0.98 La 0.2 (Ni 1 / 3 Nb 2 / 3 ) 0.15 (Mg 1 / 3 Nb 2 / 3 ) 0.21 Zr 0.3 Ti 0.34 O3+0.20wt%ZnO+0.25wt%Li2CO3+0.35wt%CeO2 Calculation Weigh Pb3O4, ZrO2, TiO2, Ni2O3, Nb2O5, Mg(OH)2 and Li2CO3, ZnO, CeO2 doped metal compounds;

[0058] B. Mixing: The raw materials are pre-mixed and then subjected to planetary ball milling. The ball milling medium is zirconium balls and deionized water. The raw materials are then placed in an oven at 150° C. and dried for 12 hours to obtain dry powder.

[0059] C. Pre-sintering: Place the dried powder in an alumina crucible and pre-sinter in a carbon rod furnace at 750°C for 3 hours to obtain a raw material powder;

[0060] D. Slurry making: the raw material powder is milled by a planetary ball mill for 3 hours, the ball milling medium is zirconium balls and deionized water, and a viscous slurry is obtained;

[0061] E. Molding: Add 8 wt% of a binder to the slurry and spray granulate it, then press it into shape, and finally keep it in a carbon rod furnace at 860° C., 880° C., 900° C., and 920° C. for 3 hours.

[0062] F. Polarization: The polarization conditions are as follows: polarization temperature is 120° C., polarization voltage is 4 kV / mm, and polarization time is 45 minutes.

[0063] Figure 1 This is a 2400x laser microscope grain photograph of the ceramic material obtained after sintering at 860°C in Example 1-4. Figure 1 It can be seen that the grain sizes of Examples 1-4 after sintering at 860° C. are uniform and the morphology is clear.

[0064] Figure 2 The XRD diffraction pattern of the ceramic material obtained after sintering at 860°C in Example 1-4 is shown in FIG. Figure 2 It can be seen that Examples 1-4 are all in the perovskite phase after sintering at 860°C.

[0065] The sintering temperature and piezoelectric parameters of the ultra-low temperature sintered high-voltage piezoelectric constant piezoelectric ceramic materials obtained in Examples 1-4 are shown in Table 1-4:

[0066] Table 1 Performance of the ceramic tiles obtained in Examples 1-4 sintered at 860°C

[0067]

[0068] Table 2 Performance of the ceramic tiles obtained in Examples 1 to 4 sintered at 880°C

[0069]

[0070] Table 3 Performance of the ceramic tiles obtained from Examples 1 to 4 sintered at 900°C

[0071]

[0072]

[0073] Table 4 Performance of the ceramic tiles obtained in Examples 1 to 4 sintered at 920°C

[0074]

[0075] The above embodiments of the present invention improve the piezoelectric performance while lowering the sintering temperature by designing the general chemical composition ratio of the material, and then doping with metal compounds mainly composed of CeO2. When CeO2 is added in small amounts, it replaces the A-site atom, hard doping, improves the structure of the piezoelectric ceramic material after sintering, and promotes grain growth, thereby reducing the sintering temperature. When CeO2 is added in large amounts, it mainly replaces the B-site atom, soft doping, and improves the piezoelectric performance. It is supplemented by low-melting compounds such as Li2CO3 and ZnO that melt between the grain boundaries in liquid form during sintering, thereby lowering the sintering temperature and improving the piezoelectric performance of the material. The present invention can reduce the minimum sintering temperature of low-temperature sintered piezoelectric ceramic materials to 860°C, and the piezoelectric constant d33≥550pC / N, and the electromechanical coupling coefficient K p ≥0.6. When the sintering temperature is increased to 920℃, the piezoelectric constant d33 is ≥650pC / N, and the electromechanical coupling coefficient K p ≥0.65.

[0076] In summary, the piezoelectric ceramic brake, piezoelectric ceramic touch screen, piezoelectric ceramic ultrasonic driver and other piezoelectric laminated ceramic devices produced by the present invention have the advantages of simple preparation process, high efficiency, low cost, high piezoelectric constant, and easy mass production.

Claims

1. A metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant, characterized in that: The general chemical formula of this material is Pb 1-x La x (Ni 1 / 3 Nb 2 / 3 ) y (Mg 1 / 3 Nb 2 / 3 ) z Zr m Ti n O3+v%MO, wherein 0.01≤x≤0.03, 0.1≤y≤0.2, 0.2≤z≤0.3, 0.2≤m≤0.3, n=1-(y+z+m), MO is a doped metal compound, and v% ranges from 0.4 to 1.0wt.%, v% represents the total doping amount of MO in PZT-based piezoelectric ceramics (Pb 1-x La x (Ni 1 / 3 Nb 2 / 3 ) y (Mg 1 / 3 Nb 2 / 3 ) z Zr m Ti n O3) weight percentage.

2. The metal compound-doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 1, characterized in that: The metal compound MO is ZnO, Li2CO3 and CeO2, the doping amount of ZnO is 0.1-0.4wt.%, the doping amount of Li2CO3 is 0.1-0.4wt.%, and the doping amount of CeO2 is 0.15-0.5wt.%.

3. The metal compound-doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 1, characterized in that: The piezoelectric constant d33 of the metal compound doped PZT-based piezoelectric ceramic material is ≥500pC / N, and the electromechanical coupling coefficient K p ≥0.

6.

4. The ultra-low temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 1, characterized in that: The sintering temperature when preparing the piezoelectric ceramic material is 860-920°C.

5. The ultra-low temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 4, characterized in that: The method comprises the following steps: (1) Ingredients: weigh the raw materials Pb3O4, ZrO2, TiO2, Ni2O3, Nb2O5, Mg(OH)2 and doped metal compounds (Li2CO3, ZnO, CeO2) according to the general chemical formula of the piezoelectric ceramic material; (2) Mixing: The weighed raw materials are pre-mixed and then subjected to planetary ball milling. The ball milling medium is zirconium balls and deionized water. After ball milling, the raw materials are dried in an oven to obtain a dry powder. (3) Pre-sintering: placing the dried powder obtained in step (2) in an alumina crucible for pre-sintering; (4) slurry preparation: the material obtained after pre-calcination in step (3) is milled in a planetary ball mill for 2 to 3 hours, the milling medium being zirconium balls and deionized water, to obtain a viscous slurry; (5) Sintering: After adding a binder to the slurry obtained in step (4) and spraying granulation, the slurry is pressed into shape and finally heated to 860-920° C. in a carbon rod furnace and kept at this temperature for 3 hours; (6) Polarization: The sintered samples were polarized under the following conditions: polarization temperature of 100-130°C, polarization voltage of 3.0-4.5 kV / mm, and polarization time of 30-50 minutes.

6. The ultra-low temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 5, characterized in that: In step (2), the drying temperature is 130-165° C. and the drying time is 10-15 hours.

7. The ultra-low temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 5, characterized in that: In step (3), pre-sintering is performed in a carbon rod furnace at 750-780° C. for 2-4 hours.

8. The ultra-low temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 5, characterized in that: In step (5), the added binder accounts for 7-10wt% of the weight of the slurry, and the binder is a polyvinyl alcohol aqueous solution with a concentration of 5-15wt.%.

9. The ultra-low temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 5, characterized in that: When the sintering temperature is 860~920℃, the piezoelectric constant d33 of the material is ≥500pC / N, K p ≥0.

6.

10. The ultra-low temperature sintering preparation method of the metal compound doped PZT-based piezoelectric ceramic material with a high piezoelectric constant according to claim 5, characterized in that: When sintered at 860℃, the piezoelectric constant d33 of the material is ≥500pC / N, K p ≥0.6, when sintered at 880℃, the piezoelectric constant d33 of the material is ≥550pC / N, K p ≥0.6, when sintered at 900℃, the piezoelectric constant d33 of the material is ≥600pC / N, K p ≥0.6, when sintered at 920℃, the piezoelectric constant d33 of the material is ≥650pC / N, K p ≥0.6.

Citation Information

Patent Citations

  • Piezoelectric ceramic with high density and high piezoelectric constant

    CN109503157A

  • Lead-lanthanum zirconate-titanate piezoelectric ceramic and preparation method thereof

    CN110015897A

  • Piezoelectric element and process for production thereof

    EP1321987A2